ijps 2021
DOI: 10.36468/pharmaceutical-sciences.770
|View full text |Cite
|
Sign up to set email alerts
|

Dichloromethane Crude Extract of Gymnanthemum extensum Combined with Low Piperine Fractional Piper nigrum Extract Induces Apoptosis on Human Breast Cancer Cells

Abstract: Faisal et al.: G. Extensum Combined with P. Nigrum Induces Apoptosis This study aims to investigate the cytotoxicity of Andrographis paniculata, Ziziphus spina-christi and Gymnanthemum extensum crude extracts and their combination with low piperine fractional Piper nigrum extract. All plants were extracted with water and five organic solvents (methanol, ethanol, dichloromethane, ethyl acetate and hexane). Cytotoxicity was assessed by 3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyl tetrazolium bromide assay on three … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 46 publications
0
1
0
1
Order By: Relevance
“…In the dichloromethane extract of Andrographis paniculata , Ziziphus spina-christi and Gymnanthemum extensum it exhibited the strongest cytotoxicity on SW-620 colorectal cancer cells (IC 50 = 7.49 µg/mL), MCF-7 cell line (IC 50 = 13.35 µg/mL) and A2780 ovarian cancer cells (IC 50 = 15.58 µg/mL), respectively. The gas chromatographic-mass spectrometry study of the dichloromethane extract of the aforementioned species identified major compounds including 1-heptatriacotanol and hexadecanoic acid ( Faisal et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…In the dichloromethane extract of Andrographis paniculata , Ziziphus spina-christi and Gymnanthemum extensum it exhibited the strongest cytotoxicity on SW-620 colorectal cancer cells (IC 50 = 7.49 µg/mL), MCF-7 cell line (IC 50 = 13.35 µg/mL) and A2780 ovarian cancer cells (IC 50 = 15.58 µg/mL), respectively. The gas chromatographic-mass spectrometry study of the dichloromethane extract of the aforementioned species identified major compounds including 1-heptatriacotanol and hexadecanoic acid ( Faisal et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…Metode penambatan molekul merupakan salah satu pendekatan dengan bantuan komputer dengan menggunakan struktur 3 dimensi dari senyawa kimia dan protein-protein yang tersedia dalam sebuah database (Luo, Xie, & Marmorstein, 2008). Penelitian kami sebelumnya mengenai ekstrak daun sambiloto ternyata menghasilkan kesimpulan bahwa ekstrak diklorometana dari daun sambiloto dapat menghambat pertumbuhan sel kanker kolorektal (HT-29 dan SW-620) (Faisal et al, 2021). Pada ekstrak tersebut kami mendapatkan 17 senyawa volatil ekstrak diklorometana daun sambiloto.…”
Section: Pendahuluanunclassified